Pola Demografi Berbasis Informasi Paten: Sebuah Kajian Gender dari Paten Terdaftar LIPI - Andi Budiansyah; Maidina Maidina (Jurnal Manajemen Teknologi, 2019)
Abstract. Intellectual Property (IP), especially patent, has an important role in the protection of technology transfer and dissemination of knowledge for the public. Indonesian Institute of Sciences (LIPI), since 2001 until 2015, has registered more than 360 patents. This study aims to study and analyze LIPI’s inventors track record based on gender gaps using quantitative approach from 2005-2014 patent registration data with a total of 287 registered patents. The results of the study reveals that the ratio between male and female inventors was 2:1. This result shows that the chance for women's innovation contribution at LIPI has the ratio that is almost the same as men. Most inventors, both men and women, were dominated by productive age of 30-34 years, with the majority having Bachelor as their educational background. Moreover, the contribution of female inventors was 33% from the total patents, with the details of the research group involving women was 56%. Nevertheless, most inventions were dominated by the Deputy of Engineering Science, which was 66%, was also dominated by men. Keywords: Intellectual property, gender, registered patent, knowledge dissemination, management, demographic factor, productivity,  Abstrak. Kekayaan Intelektual (KI) khususnya paten, memiliki peran penting dalam perlindungan alih teknologi dan diseminasi pengetahuan untuk masyarakat. Lembaga Ilmu Pengetahuan Indonesia (LIPI) sejak tahun 2001 sampai 2015 telah mendaftarkan lebih dari 360 paten. Penelitian ini bertujuan untuk mengkaji dan menganalisa rekam jejak inventor LIPI berdasarkan gap gender dengan pendekatan kuantitatif pada data pendaftaran paten 2005 – 2014 dengan jumlah 287 paten terdaftar. Hasil kajian mengungkapkan pada rentang tahun 2005-2014, perbandingan antara inventor laki-laki dan perempuan adalah sebesar 2:1. Hasil ini menunjukkan kesempatan kontribusi inovasi perempuan di LIPI memiliki rasio yang hampir sama dengan laki-laki. Inventor terbanyak baik laki-laki maupun perempuan didominasi pada umur produktif 30–34 tahun dengan mayoritas berlatar belakang pendidikan S-1. Adapun kontribusi inventor perempuan adalah sebesar 33% dari keseluruhan total paten dengan rincian kelompok penelitian yang melibatkan perempuan sebesar 56%. Adapun invensi terbanyak didominasi oleh kedeputian IPT yaitu sebanyak 66% yang juga didominasi oleh laki-laki.Kata kunci: Kekayaan intelektual, gender, paten terdaftar, diseminasi pengetahuan